IMPACT study on intervening with a manualised package to achieve treatment adherence in people with tuberculosis: protocol paper for a mixed-methods study, including a pilot randomised controlled trial. Issue 12 (17th December 2019) - Stagg, Helen R; Abubakar, Ibrahim; Campbell, Colin NJ; Copas, Andrew; Darvell, Marcia; Horne, Robert; Kielmann, Karina; Kunst, Heinke; Mandelbaum, Mike; Pickett, Elisha; Story, Alistair; Vidal, Nicole; et al.
Abstract : Introduction: Compared with the rest of the UK and Western Europe, England has high rates of the infectious disease tuberculosis (TB). TB is curable, although treatment is for at least 6 months and longer when disease is drug resistant. If patients miss too many doses (non-adherence), they may transmit infection for longer and the infecting bacteria may develop resistance to the standard drugs used for treatment. Non-adherence may therefore risk both their health and that of others. Within England, certain population groups are thought to be at higher risk of non-adherence, but the factors contributing to this have been insufficiently determined, as have the best interventions to promote adherence. The objective of this study was to develop a manualised package of interventions for use as part of routine care within National Health Services to address the social and cultural factors that lead to poor adherence to treatment for TB disease. Methods and analysis: This study uses a mixed-methods approach, with six study components. These are (1) scoping reviews of the literature; (2) qualitative research with patients, carers and healthcare professionals; (3) development of the intervention; (4) a pilot randomised controlled trial of the manualised intervention; (5) a process evaluation to examine clinical utility; and (6) a cost analysis. Ethics and dissemination: This study received ethics approval on 24 December 2018 from Camberwell St. Giles Ethics Committee, UK (REC reference 18/LO/1818). Findings will be published and disseminated through peer-reviewed publications and conference presentations, published in an end of study report to our funder (the National Institute for Health Research, UK) and presented to key stakeholders. Trial registration number: ISRCTN95243114 Secondary identifying numbers: University College London/University College London Hospitals Joint Research Office 17/0726. National Institute for Health Research, UK 16/88/06.